Exploring User Experiences with E-wallet DANA among Indonesian Millennials: E-satisfaction and E-loyalty Analysis - Ina Kartika Wati; Abdul Mukti Soma; Heri Ispriyahadi (Research Synergy Foundation, 2024)
Millennials have been significantly shaped by advancements in internet technology, affecting their preferences and behaviors. This generation is characterized by comfort with digital tools, multitasking abilities, and a preference for flexibility. As technology evolves, millennials will also encounter challenges like the Fear of Missing Out (FOMO), which is particularly evident in the financial sector, which drives the adoption of digital payment systems and fintech solutions. This study analyzes millennial satisfaction with DANA, a prominent digital payment system in Indonesia, and investigate how satisfaction predicts loyalty. Using a quantitative approach, data were collected from 150 respondents, all of whom were millennials, using DANA via Google Forms on a 5-point Likert scale. This study employed Partial Least Squares (PLS) statistics to examine the correlation between customer satisfaction and loyalty. The results reveal a strong positive correlation, underscoring the importance of user satisfaction as a key driver of loyalty. These findings provide valuable insights for developing marketing strategies and enhancing customer retention in the digital payment industry.